Endocrine dysfunction in transfusion dependent thalassemia patients from central India - Roshan Saras,; Anjali Bharani,; Gunvant Singh Eske,; Nilesh Jain, (Asian Journal of Medical Sciences, 2023)
Background: Thalassemia refers to a group of genetically inherited diseases characterized by decreased or absent synthesis of normal globin chains resulting in defective globin chains. Most of the available studies in the literature have been done in adults and there is a paucity of studies highlighting the prevalence of hormonal dysfunction in transfusion dependent patients in pediatric age group. We conducted the present study with an aim to estimate the prevalence of hormonal dysfunction in transfusion dependent thalassemia (TDT) patients at a tertiary care center of Central India. Aims and Objectives: The aim of the study was to estimate the prevalence of hormonal dysfunction in TDT patients at a tertiary care center of central India. Materials and Methods: It is descriptive cross-sectional study conducted at tertiary care hospital MGM Medical College, Indore, Madhya Pradesh, conducted over a period of 12 months (August 2021–July 2022). Results: Our study recruited a total of 100 children with age ranging from 9 year to 18 years with the mean age of 13.16±2.86 years. Sixty percent (n=60) of our study population were males and 40% (n=40) were females. The prevalence of hypogonadism was 35.18% analyzed in 54 patients, hypothyroidism was 10%, and diabetes was 5%. Although serum ferritin was very elevated in all patients with endocrine dysfunction; statistically significant association was found between serum ferritin and hypothyroidism (P=0.020). Conclusion: Patients with TDT are often associated with endocrinopathies; most commonly hypogonadism, followed by hypothyroidism and diabetes. Early screening and treatment is necessary to improve their outcome.